A comprehensive evaluation of digestate gasification in biogas atmospheres towards the integration of anaerobic digestion and gasification - Rui Zhang; Zhuang Yuan; Hongru Li; Zhi Wang; Shengquan Zhou; Xiaochao Zhu; Zhanjun Cheng; Beibei Yan (Bioresource Technology, 2026)

Unveiling shear-induced non-uniform deformation of segmented tunnels through fully instrumented model tests - Yi Zhou; Hong-Hu Zhu; Dao-Yuan Tan; Jing-Wu Huang; Zhen-Rui Yan; Wan-Huan Zhou (Tunnelling and Underground Space Technology, 2026)

Linear resistance but threshold-controlled recovery of vegetation to compound heatwave–drought extremes - Shuang Zhou; Shaohong Wu; Jiangbo Gao; Lulu Liu; Rui Yan; Jie Wang; Bin Li (Global and Planetary Change, 2026)

Spatiotemporal variation in seed density influences rodent-mediated seed dispersal of Juglans mandshurica in secondary forests - Rui Liu; Shitong Gao; Minghui Zhou; Qiaoling Yan (Forest Ecology and Management, 2026)

Constructing a dual-active-phase Li4SiO4/Li3NaSiO4 system through Na2CO3/NaCl codoping for enhanced thermochemical energy storage - Jian Chen; Rui Shen; Yan Qi; Hanlei Yu; Tao Fang; Xue Bu; Ziheng Xu; Han Ye; Youshi Li; Bocheng Yu; Hui Zhou (Chemical Engineering Journal, 2026)

Environmental and physiological regulation of evapotranspiration key parameters and subsequent modeling in a rain-fed maize field, Northeast China - Rongxuan Bao; Haofang Yan; Jianyun Zhang; Guoqing Wang; Chuan Zhang; Desheng Zhang; Yudong Zhou; Biyu Wang; Yujing Han; Youwei Liu; Xuanxuan Wang; Rui Zhou (Journal of Hydrology, 2026)

Electronic, optical and mechanical properties, and photocatalytic water splitting of Janus ZrHfCO2 under biaxial strain: First-principles prediction - Rui-Wen Yan; Hao Zhang; Xiao-Hong Li; Rui-Zhou Zhang; Hong-Ling Cui (Journal of Environmental Chemical Engineering, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Dietary ellagic acid improves glucose and lipid homeostasis with concurrent gut microbiota and serum metabolome remodeling in db/db mice - Rui-Bo Jia; Weipei Li; Pengru Yan; Chunxia Zhou; Zirui Huang; Mouming Zhao (Food Bioscience, 2026)

Subchronic PM2.5 exposure exacerbates chronic stress-induced depression-like pathology in mice - Haoyu Lu; Xiaohui Zhao; Ran Ning; JunKoo Yi; Zhongmei He; Yan Zhao; Jianan Geng; Jia Zhou; Weijia Chen; Rui Du (Environmental Research, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

N-myristoyl Transferase Maintains Type II Neuroblasts through Notch Signaling in Drosophila - Sifan Gong; Shuliu Zhang; Xu Yan; Wenting Gong; Qingxia Zhou; Xiaojing Yang; Kun Yang; Menglong Rui; Su Wang (Neuroscience Bulletin, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Whole-genome sequencing uncovers the extreme adaptation mechanisms of Pseudomonas sp. Ma2–10 screened from the Antarctic sea sediment near King George Island - Rui Deng; Yuanfang He; Xiying Zhang; Guofang Wang; Shunan Ma; Shigan Yan; Mingyang Zhou (Marine Genomics, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Nanoflower-like Co3S4/FeOOH heterostructure enables efficient norfloxacin degradation via synergistic radical-non-radical PMS activation - Yuerong Zhou; Ming Yi; Yu Zhao; Rui Yang; He Yan; Xiuwen Cheng (ENGINEERING Environment, 2026)

Identification, expression, and insecticidal activity analysis of a novel cry toxin gene from Bacillus thuringiensis Gxun777-1 - Qi Gao; Tianbao Yang; Xixi Li; Rui Chen; Mingguo Jiang; Yan Zhou (World Journal of Microbiology and Biotechnology, 2026)

Integrating distributed hydrologic simulation with low-flow resilience: a spatiotemporal perspective - Yan Zhou; Chi Zhang; Rui Hao; Yongxin Liao; Wei Yin; Dianchang Wang (Journal of Hydrology, 2026)

Zircon thermal annealing ages determine a late Eocene birth for the First Bend of the Yangtze River - Yang Zhang; Rui Li; Guang-Yan Zhou; David Chew; Jian-Ping Zheng; Qing Xiong; Wei Wang (Earth and Planetary Science Letters, 2026)

Establishment and application of multiple cross displacement amplification coupled with lateral flow biosensor (MCDA-LFB) for visual and rapid detection of Candida glabrata - Yan Yuan; Yuhong Zhou; Yanfeng Zhou; Rui Ye; Jingrun Lu; Yizhe Wang; Fang Wei; Fukuan He; Honglan Yu; Yu Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Estimation of daily net radiation based on the continuous meteorological data observed from different underlying surfaces - Rongxuan Bao; Haofang Yan; Chuan Zhang; Guoqing Wang; Jianyun Zhang; Desheng Zhang; Yudong Zhou; Biyu Wang; Xuanxuan Wang; Rui Zhou; Youwei Liu; Yujing Han (Climate Dynamics, 2026)

SIRT1-regulated mitophagy mitigates lipotoxicity-induced ferroptosis in diabetic kidney disease - Yingchun Jian; Yongqin Zeng; Zhengdi Wang; Xingyan Zhou; Haiping Zhang; Dan Liang; Rui Yan (Apoptosis, 2026)

Evaluating the environmental impact of hydrothermal cracking solid organic fertilizer: Carbon and nitrogen retention and toxic metals analysis - Rui Xia; Xiao-xiao Yang; Jue Wang; Kai-le Li; Zhi-peng Sun; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Journal of Environmental Sciences, 2026)

Construction and textural modification of soft surimi gel from spanish mackerel (Scomberomorus niphonius) by polysaccharides - Yin-Yin Lv; Xian-Hao Zhang; Jia-Ni Zhou; Ying-Rui Wang; Zhu-Jun Zhang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2026)

Multi-frequency controlled-source electromagnetic fast forward modeling in general anisotropic media - Hang-rui Shen; Feng Zhou; Zhi-yong Zhang; Yan Li; Hui Chen; Ying-ying Zheng; Hai-long Ye (Applied Geophysics, 2026)

Corrigendum to “Silica nanoparticles induce cardiac injury and dysfunction via ROS/Ca2+/CaMKII signaling” [Sci. Total Environ., 837 (2022), 155733] - Yi Qi; Hailin Xu; Xueyan Li; Xinying Zhao; Yan Li; Xianqing Zhou; Rui Chen; Yanbo Li; Zhiwei Sun; Caixia Guo (Science of The Total Environment, 2026)

Understanding the migration and transformation characteristics of Cr3+ in the hydrothermal cracking of biomass model components - Rui Xia; Kai-le Li; Peng Zhao; Xiao-xiao Yang; Jue Wang; Ke-wen An; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Biomass and Bioenergy, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

An enhanced GNSS/INS positioning method with position and attitude constraints in urban environments - Jianhui Cui; Xuan Han; Rufei Liu; Rui Tu; Yan Xiang; Shuangshuang Wu; Zeyu Li; Wenqian Zhou (GPS Solutions, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Activation of PMS for tetracycline removal by waste-derived FeOOH/Fe3O4 magnetic nanocomposites: Ecotoxicity calculations and mechanism analysis - Shengwen Zhou; Rui Yang; He Yan; Guixian Zhu; Xingwu Lu; Xiuwen Cheng (Journal of Water Process Engineering, 2026)

A unified hybrid deterministic-stochastic inversion methodology - Chao Zhuang; Long Yan; Huiyang Qiu; Rui Hu; Jiangbo Han; Huan Song; Zhifang Zhou; Jinguo Wang; Walter A. Illman (Journal of Hydrology, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

The efficient removal of dolomite from phosphate ores using a novel collector: Flotation selectivity and collecting mechanism - Yifan Zhang; Yudi Yan; Bingqiao Yang; Rui Ma; Yang Xu; Huihua Luo; Fang Zhou (Minerals Engineering, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Start-up and operational strategies for side-stream nitrification reactors in a cyclic up-concentration nitrogen recovery process: Enhancing targeted nitrate conversion and deciphering nitrogen metabolism - Molin Lian; Zihang Ma; Guang Chen; Xiangdong Xu; Rui Tang; Shikun Yan; Yu Wang; Yuyue Zhang; Zhen Zhou (Chemical Engineering Journal, 2025)

Deep structure of the middle segment of the Bangong-Nujiang Suture Zone based on aerogravity and aeromagnetic anomalies, Qinghai-Tibet Plateau - Bao-bao Cao; Dao-qing Zhou; Yan-yan Wei; Rui Zhao; Qiao-juan Yan; Lei Xu; Di-shuo Zhang (Applied Geophysics, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Efficient degradation mechanism of fomesafen by earthworms and gut degrading bacteria synthetic community - Yan Ge; Aoqi Yang; Yongkang Dong; Siqi Wang; Rui Xu; Dongxing Zhou (Pesticide Biochemistry and Physiology, 2025)

The correlation between temperature change and lung cancer risk altered by air particulate pollutants: Nationwide analysis - Shenxuan Zhou; Yanchi Wang; Zhenyu Li; Yiran Liu; Rui Zhu; Bo Liu; Jiacan Yuan; Mingna Wu; Jing Xiao; Hanpeng Lai; Anhui Ning; Yan Zhang; et al. (Journal of Cleaner Production, 2025)

A novel interpolation method for high temporal-resolution electricity usages based on volatility quantification and pattern extraction - Yinao Zhou; Ruoxi Geng; Xuyuan Kang; Huiming Xu; Xiao Wang; Rui Li; Da Yan (Energy and Buildings, 2025)

Construction of a gradient cross-linked nanofiltration membrane with quaternized surface for efficient heavy metal removal - Rui Hou; Pei Wang; Chao Cheng; Jianlong Dai; Wentao Yan; Yong Zhou; Congjie Gao (Desalination, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

The Reliability of Offshore Jacket Platforms Based on Bayesian Calibration - Fang Zhou; Fansheng Meng; Yuhan Zhao; Jinbo Chen; Rui Zhao; Yongfei Zhang; Zhaolong Han; Yan Bao (Journal of Marine Science and Engineering, 2025)
The safety of offshore structures is a key topic in developing offshore oil and gas and offshore wind energy. Due to the harsh offshore environment and costly offshore field tests, offshore field trials to validate the theoretical models for offshore structures are limited, and testing results can rarely be found in the public domain. The Bayesian updating technique combines existing engineering knowledge with the observed performance data about in-service offshore structures to update model uncertainties. Hence, the Bayesian technique overcomes the shortcomings of limited offshore field trials. This paper compiles performance data on offshore jackets in hurricanes in the Gulf of Mexico (GoM) in the past two decades and calibrates the model uncertainties of the API method using the Bayesian technique. With the updated model uncertainty, this paper evaluates the reliability of generic offshore jackets in the GoM and the case study’s offshore wind substation in China. With a typical reserve strength ratio (RSR) of about 2.0 to 2.2, the reliability analysis reveals that the updated annual failure probability of a generic offshore jacket in the GoM is largely less than 1.0×10−3, indicating that the extreme weather overload is not a major concern. However, the RSR of the case study platform in China is greater than 4.5, and the annual failure probability for the case study offshore wind substation is about 2–3 orders of magnitude lower than typical oil and gas jackets. Hence, from the extreme metocean condition perspective, the substation under investigation has sufficient structural capacity, and the design practice for offshore wind substations in northern China may be improved.

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

One-billion-year-old eukaryotic algal fossil Arctacellularia from North China and its implications for the evolution of pre-Cryogenian filamentous multicellularity - Rui Huang; Guangjin Li; Jiayue Wang; Qing Tang; Mingyang Qiu; Qian Chen; Hanzhi Qu; Chengxi Wu; Wenfei Cui; Xianqin Yan; Chuanming Zhou; Xunlai Yuan; et al. (Precambrian Research, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Electroacupuncture may alleviate inflammatory pain by downregulating the expression of P2Y14 receptor in the primary somatosensory cortex - Shuai Hou; Cui-Yuan Chen; Rui-Zhu Zhou; Liu-Xuan He; Xiao-Xiao Zhao; Sha-Sha Chen; Sha Yang; Hai-Yan Yin; Shu-Guang Yu (Purinergic Signalling, 2025)

Effects of long-term vegetation restoration on soil aggregate and aggregate-associated nutrient stoichiometry of desertified grassland on the eastern Qinghai–Tibet Plateau - Zhong Du; Rui Zhou; Yan Chen; Enran Zhan; Youjun Chen; Huan Zheng; Dongzhou Deng; Li He; Dechao Chen; Huijun Gao; Yiqun Liu (Agriculture, Ecosystems & Environment, 2025)

An automatic landmarking algorithm for leaf morphology based on conformal mapping - Peige Zhong; Xiaojun Liu; Yulu Ye; Rui Zhang; Hu Zhou; Yan Guo; Baoguo Li; Jinyu Zhu; Yuntao Ma (Computers and Electronics in Agriculture, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Spatiotemporal prediction of ionospheric TEC based on denoising wavelet transform convolution - Rui Zhou; Yanxiong Wu; Jianxian Cai; Haijun Liu; Huijun Le; Jian Xiao; Yan Ma (GPS Solutions, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Corrigendum to “N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater” [Chem. Eng. J. 491 (2024) 151763] - Pin Peng; Lixiang Chen; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Label-free urinary protein detection through machine learning analysis of single droplet evaporation patterns - Ruyue Yang; Nannan Cao; Yan Yang; Shujuan Guan; Chao Yang; Bo Situ; Yongyu Rui; Hongwei Zhou; Lei Zheng (Analytica Chimica Acta, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Different effects of bio/non-degradable microplastics on sewage sludge compost performance: Focusing on antibiotic resistance genes, virulence factors and key metabolic functions - Xiangyu Liu; Huiyue Li; Jie Yang; Shen Yan; Yufei Zhou; Rui Jiang; Renhe Li; Mengmeng Wang; Peng Ren (Journal of Hazardous Materials, 2025)

Study on the improvement of Rye bread quality by bacterial Laccase derived from Streptomyces coelicolor - Ran Zhang; Yanhua Li; Yuan Gao; Fengyun Wang; Peng Zhou; Yan Zhang; Ying Li; Kaiyue Wang; Ting Rui; Guilan Zhu; Jingjing Wang; Zemin Fang (Journal of Cereal Science, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Mitophagy impairment drives microglia activation and results in cognitive deficits in neonatal mice following sevoflurane exposure - Piao Zhang; Rui-Juan Cheng; Qiao-Ling Yang; Yan Gong; Yan Xu; Ling-Min Chen; Li Zhou; Chun-Ling Jiang (Toxicology Letters, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

Effects of alternating wet and dry irrigation regimes on rice growth and physiology characteristics in southeast China - Rui Zhou; Haofang Yan; Chuan Zhang; Xingye Zhu; Guoqing Wang; Bin He; Kinda Negessa Disasa; Imran Ali Lakhiar; Run Xue; Yudong Zhou; Biyu Wang; Jun Li; et al. (Paddy and Water Environment, 2025)

Evaluation of natural products from virtual screenings as SARS-CoV-2 main protease inhibitors using combinational experiments - Jiahao Zhou; Rui Zhang; Haohao Yan; Xiaoping Liu; Chao Shang; Yunyu Chen (Natural Product Research, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Bacterial cellulose-based scaffold modified with anti-CD29 antibody to selectively capture urine-derived stem cells for bladder repair - Tianyi Shao; Mingzhe Yan; Rui Liu; Yanming Zhang; Banghui Wang; Yifei Li; Yuxin Liu; Danxia Li; Lixin Jin; Bingcheng Yi; Qihui Zhou (Carbohydrate Polymers, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Prediction of sandstone porosity in coal seam roof based on variable mode decomposition and random forest method - Ya-ping Huang; Xue-mei Qi; Yan Cheng; Ling-ling Zhou; Jia-hao Yan; Fan-rui Huang (Applied Geophysics, 2025)

Equol promotes the in vitro maturation of porcine oocytes by activating the NRF2/KEAP1 signaling pathway - Sai Xiao; Ke Peng; Rui Chen; Xinxin Liu; Benliang Zhou; Rijing He; Yujun Yan; Runtian Wan; Ye-Shi Yin; Shengsheng Lu; Xingwei Liang (Theriogenology, 2025)

Efficient simultaneous degradation of multiple sulfonamide antibiotics in soil using biocarbon-based nanomaterials as catalysts for persulfate activation - Meng-zhou Wang; Rui Liu; Jin-yan Yang; Aleksander Nikitin (Science of The Total Environment, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Atomically dispersed iron & iron clusters synergistically accelerate electrocatalytic ammonia synthesis - Haoran Zhang; Yuelong Liu; Sanshuang Gao; Haijian Wang; Rui Bai; Yan Zhao; Yingtang Zhou; Guangzhi Hu; Xue Zhao (Chemical Engineering Journal, 2025)

Secular evolution of continental crust of the North China Craton constrained by U-Pb and Lu-Hf-O/Sm-Nd isotopic analyses of detrital zircon and monazite in river sediments - Guangyan Zhou; D. Graham Pearson; Yan Luo; Long Li; Christopher M. Fisher; Rui Li; Wei Wang; Yuanbao Wu (Chemical Geology, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Controllable construction of ratiometric fluorescent probe based on Ag/Au nanoclusters and silicon nanoparticles for multivariate detection of Ag+, Cu2+, and Hg2+ - Jingyu Pang; Linan Zhou; Zhuang Liang; Tingting Li; Rui Yan; Fang Chai (Journal of Environmental Chemical Engineering, 2024)

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Comprehensive compositional analysis of liquid organic product prepared by industrialized hydrothermal cracking of biomass waste and its potential application as fertilizer - Rui Xia; Jue Wang; Xiao-xiao Yang; Qing-hai Li; Hui Zhou; Hui Sun; Yan-guo Zhang (Science of The Total Environment, 2024)

Increased stress from compound drought and heat events on vegetation - Shuang Zhou; Shaohong Wu; Jiangbo Gao; Lulu Liu; Delong Li; Rui Yan; Jie Wang (Science of The Total Environment, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Portulaca oleracea L. polysaccharide ameliorates ulcerative colitis by regulating the immune system and gut microbiota - Yang Yang; Xiechen Zhou; Guiyan Jia; Hui Zhao; Yan Li; Junyang Cao; Zijian Guan; Rui Zhao (Food Bioscience, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Global research trends in Rhizodeposition-mediated soil carbon cycle: A bibliometric analysis - Dongming Chen; Fei Yan; Xuemei Fang; Jiqiong Zhou; Xingpeng Hu; Xiaoming Ma; Xin Zheng; Rui Yin; Feida Sun; Yanfu Bai; Zhouwen Ma; Yakov Kuzyakov; et al. (Applied Soil Ecology, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Outdoor tubular photobioreactor microalgae-microorganisms biofilm treatment of municipal wastewater: Enhanced heterotrophic assimilation and synergistic aerobic denitrogenation - Pan Li; Yajun Luo; Jiansong Tian; Yiwei Cheng; Shiji Wang; Xin An; Jingxian Zheng; Heng Yan; Hongtao Duan; Jin Zhang; Zhicheng Pan; Yangwu Chen; et al. (Bioresource Technology, 2024)

Biocontrol potential of Priestia megaterium YB-3 against Meloidogyne graminicola and its impact on the rhizosphere microbial community - Shan Ye; Yihang Ma; Siyu Zhou; Rui Yan; Zhuhong Yang; Zhong Ding (Journal of Pest Science, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Zircon U–Pb geochronology and geochemistry of Paleoproterozoic quartz monzonite in the Northern Yangtze Craton: Petrogenesis and geological implications - Wen-Xiang Zhang; Rui Li; Guang-Yan Zhou; Zhi-Fu Liu; Yuan-Bao Wu (Precambrian Research, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

The potential regulatory role of the non-coding RNAs in regulating the exogenous estrogen-induced feminization in Takifugu rubripes gonad - Xufang Shen; Hongwei Yan; Mingtao Hu; Huiting Zhou; Jia Wang; Rui Gao; Qi Liu; Xiuli Wang; Ying Liu (Aquatic Toxicology, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

The non-linear associations between blood manganese level and sarcopenia in patients undergoing maintenance hemodialysis: A multicenter cross-sectional study - Rui Hu; Qiangying Zeng; Qingdong Xu; Hongmei Zhou; Rongshao Tan; Xiaoshi Zhong; Yan Liu; Yi Li; Yun Liu (Journal of Trace Elements in Medicine and Biology, 2024)

N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater - Pin Peng; Lixiang Chen.; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2024)

Invalidation of geraniin as a potential inhibitor against SARS-CoV-2 main protease - Rui Zhang; Haohao Yan; Jiahao Zhou; Xiaoping Liu; Yunyu Chen (Natural Product Research, 2024)

Cu-II-directed self-assembly of fullerenols to ameliorate copper stress in maize seedlings - Chenjie Fan; Qingyuan Liang; Yan Wang; Peimei Chen; Jiakai Wu; Qingnan Wu; Shijun Jiang; Yang Zhou; Rui He; Fuju Tai (Science of The Total Environment, 2024)

Ammonium addition reduces phosphorus leaching in a long-term mineral or organic fertilized calcareous soil during flooding conditions - Lulu Wei; Yan Zhou; Guiming Yin; Jianyu Cui; Junhui Yin; Rui Liu; Qing Chen; Shuai Zhang (Journal of Environmental Management, 2024)

Pyrite/biochar-activated peroxymonosulfate strengthens tetracycline degradation: Important roles of surface functional groups and Fe(Ⅱ)/Fe(Ⅲ) redox cycling - Jieru Fang; Fang He; Zelong Yan; Jingjing Wang; Rui Yu; Haihong Zhou (Journal of Environmental Chemical Engineering, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Snakehead vesiculovirus (SHVV) leader RNA interacts with host antiviral factors RPS8 and L13a and promotes virus replication - Yan Ji; Rui Cheng; Xuan Zhou; Jiaqi Zhang; Xiaodan Liu; Suhong Sheng; Chi Zhang (Fish & Shellfish Immunology, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Seedless hydrothermal growth of piezoelectric photocatalytic ZnO nanowires on laser-ablated copper mesh for oil/water separation - Xiaohan Xing; Rui Zhou; Huangping Yan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2024)

Experimental analysis of a CO2 closed heat pump drying system combined with rotary dehumidification for drying banana slices drying - Zhili Sun; Qianqian Wang; Yingying Yuan; Dandan Wang; Qiang Zhou; Chunwei Xu; Kexin Meng; Haowei Peng; Lei Yan; Rui Jin; Lei Li; Haowei Liu; et al. (International Journal of Refrigeration, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

Two-dimensional peak-valley alternating self-supporting electrode accelerating nitrate electrocatalytic reduction: Ammonia synthesis and wastewater treatment - Yuelong Liu; Haoran Zhang; Rui Bai; Haijian Wang; Yan Zhao; Yingtang Zhou; Xue Zhao (Chemical Engineering Journal, 2024)

Long-term straw return to a wheat-maize system results in topsoil organic C saturation and increased yields while no stimulating or reducing yield-scaled N2O and NO emissions - Zhisheng Yao; Yanqiang Wang; Rui Wang; Xiaogang Wang; Yan Wang; Xunhua Zheng; Chunyan Liu; Bo Zhu; Minghua Zhou; Yan Liu; Klaus Butterbach-Bahl (Agricultural and Forest Meteorology, 2024)

Removing refractory organic substances from landfill leachate using a nanofiltration membrane bioreactor: Performance and mechanisms - Chu Zhou; Na Li; Wenbin Guo; Rui Wang; Yaohua Yan; Senlin Shao (Chemical Engineering Journal, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Effect of simplified inoculum agent on performance and microbiome during cow manure-composting at industrial-scale - Weiwei Dong; Rui Zhou; Xudong Li; Hua Yan; Jinshui Zheng; Nan Peng; Shumiao Zhao (Bioresource Technology, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Recognizing topological attributes and spatiotemporal patterns in spotted seals (Phoca largha) trophic networks based on eDNA metabarcoding - Yan Xu; Fei Huang; Mingliang Zhou; Rui Gu; Jie Zhu; Qiangqiang Rong; Yanpeng Cai (Frontiers in Marine Science, 2023)
Spotted seals, a protected species, face multifaceted threats to their habitat, which in turn impact the closely associated trophic networks. These threats will lead to irreversible structural variations within the ecosystem. Therefore, investigating the topological variability of trophic networks in spotted seals is important. Applying environmental DNA methods, field sample collection was conducted in 2021 during both the sea fishing moratorium period and the fishing period to decode fish diversity. Assessing the current status of fish resources by using the multivariate statistics approach. Applying dietary information establishes the spotted seals’ trophic network. Selecting 12 network indexes to analyze the spatiotemporal patterns of network topological attributes. As a result, about 51 families, and 76 genera species were identified. During the sea fishing moratorium and the fishing period, there are 12 and 18 different food resources available for spotted seals, respectively. The diversity index revealed that the FP had greater species richness and diversity than the SP. Comparatively, the Fishing period exhibited higher species richness and biodiversity, likely influenced by habitat heterogeneity and anthropogenic activities. Additionally, the topological features of networks reflected the high clustering coefficients (CC=0.35) and the proportion of omnivorous species (O≈60%), indicating that the network structure in this region tends to form higher trophic-level clustering patterns, which facilitate the formation of weaker interactions between clusters, enhancing the robustness of the network. The higher connectivity complexity index during the fishing period (SC=12.3) supported that the spotted seal’s trophic network was relatively more stable in this period. Thus, during the fishing period, it is crucial to pay more attention to the intensity of human fishing on mid-to-high trophic-level omnivorous fish resources to ensure the sustainability of these potential food resources for spotted seals. This comprehensive study achieved three key objectives: (a) utilizing eDNA to characterize fish diversity during distinct periods, (b) establishing trophic networks of spotted seals, and (c) discerning topological attributes and spatiotemporal patterns within the ecological network. Overall, this study can provide technical and data support for integrated ecological network management and propose suggestions for protecting and recovering spotted seals.

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Insights of microalgal municipal wastewater treatment at low temperatures: Performance, microbiota patterns, and cold-adaptation of tubular and aeration column photobioreactors - Jiansong Tian; Pan Li; Yajun Luo; Heng Yan; Jian Liu; Zhicheng Pan; Yangwu Chen; Rui Wang; Yiwei Cheng; Houzhen Zhou; Junjie Li; Xin Li; et al. (Chemosphere, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Effect of Triton X-100 on Shiraia laccase production and its application in triclosan biodegradation - Rui Peng Cong; Yan Hua Guo; Jian Qin Zhou; Jian Wen Wang (Sustainable Chemistry and Pharmacy, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Zero-valent cobalt and oxygen vacancy rich catalyst derived from Ni/Co metal-organic framework nanosheets for enhanced oxidation of aqueous contaminants via peroxymonosulfate activation - Haodong Hu; Xinlong Yan; Qingxun Hu; Xiaoyan Hu; Rui Feng; Tianbo Li; Wei Zhou; Liping Wang (Journal of Environmental Chemical Engineering, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Characteristics of annual NH3 emissions from a conventional vegetable field under various nitrogen management strategies - Yan Wang; Zhisheng Yao; Yanqiang Wang; Guangxuan Yan; Baldur Janz; Xiaogang Wang; Yang Zhan; Rui Wang; Xunhua Zheng; Minghua Zhou; Bo Zhu; Ralf Kiese; et al. (Journal of Environmental Management, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Structural characteristics of the moss (bryophyte) layer and its underlying soil structure and water retention characteristics - Xia Hu; Zhou Gao; Xiao-Yan Li; Rui-Zhe Wang; Yuan-Ming Wang (Plant and Soil, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Efficient Adsorption of Anionic Azo Dye in Wastewater with Medulla tetrapanacis Modified by Cationic Surfactant - Lianpeng Yan; Keming Zhou; Rui Zhang; Xuedong Zhu (Water, Air, & Soil Pollution, 2023)

International Nuclear Medicine Consensus on the Clinical Use of Amyloid Positron Emission Tomography in Alzheimer’s Disease - Mei Tian; Chuantao Zuo; Ali Cahid Civelek; Ignasi Carrio; Yasuyoshi Watanabe; Keon Wook Kang; Koji Murakami; Valentina Garibotto; John O. Prior; Henryk Barthel; Yihui Guan; Jiaying Lu; et al. (Phenomics, 2023)
Alzheimer’s disease (AD) is the main cause of dementia, with its diagnosis and management remaining challenging. Amyloid positron emission tomography (PET) has become increasingly important in medical practice for patients with AD. To integrate and update previous guidelines in the field, a task group of experts of several disciplines from multiple countries was assembled, and they revised and approved the content related to the application of amyloid PET in the medical settings of cognitively impaired individuals, focusing on clinical scenarios, patient preparation, administered activities, as well as image acquisition, processing, interpretation and reporting. In addition, expert opinions, practices, and protocols of prominent research institutions performing research on amyloid PET of dementia are integrated. With the increasing availability of amyloid PET imaging, a complete and standard pipeline for the entire examination process is essential for clinical practice. This international consensus and practice guideline will help to promote proper clinical use of amyloid PET imaging in patients with AD.

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Atmospheric ammonia in China: Long-term spatiotemporal variation, urban-rural gradient, and influencing factors - Jinyan Dong; Baojie Li; Yan Li; Rui Zhou; Cong Gan; Yongqi Zhao; Rui Liu; Yating Yang; Teng Wang; Hong Liao (Science of The Total Environment, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

The RLCK–VND6 module coordinates secondary cell wall formation and adaptive growth in rice - Shaoxue Cao; Yan Wang; Yihong Gao; Rui Xu; Jianing Ma; Zuopeng Xu; Keke Shang-Guan; Baocai Zhang; Yihua Zhou (Molecular Plant, 2023)

An approach for carbon content measurement in marine sediment: Application of organic and elemental carbon analyzer - Weifeng Wu; Haoshuai Li; Nan Wang; Xuan Huo; Guoqiang Zhong; Longhai Zhu; Jingyu Liu; Yang Zhou; Caiqing Yan; Rui Bao (Marine Environmental Research, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

New methylene blue-mediated photodynamic inactivation of multidrug-resistant Fonsecaea nubica infected chromoblastomycosis in vitro - Mengxue Zheng; Xiaoqing Zhou; Jiayin Pang; Zengjun Yang; Yongzhen Zou; Lian Zhang; Yan Xu; Rui Yin (Brazilian Journal of Microbiology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A corrected p-y curve model for large-diameter pile foundation of offshore wind turbine - Xiao-ling Zhang; Rui Zhou; Guo-liang Zhang; Yan Han (Ocean Engineering, 2023)

Thickness-dependent release of microplastics and phthalic acid esters from polythene and biodegradable residual films in agricultural soils and its related productivity effects - Aimee Grace Uzamurera; Peng-Yang Wang; Ze-Ying Zhao; Xiu-Ping Tao; Rui Zhou; Wen-Ying Wang; Xiao-Bin Xiong; Song Wang; Kiprotich Wesly; Hong-Yan Tao; You-Cai Xiong (Journal of Hazardous Materials, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Efficient removal of Cr(VI) by the modified biochar with chitosan schiff base and MnFe2O4 nanoparticles: Adsorption and mechanism analysis - Ling Yan; Weijuan Guo; Binbin Huang; Yujun Chen; Xinyu Ren; Yiyang Shen; Yefeng Zhou; Rui Cheng; Jie Zhang; Muqing Qiu; Baowei Hu (Journal of Environmental Chemical Engineering, 2023)

Circ_HIPK3 Inhibits H2O2-Induced Lens Epithelial Cell Injury in Age-Related Cataract Depending on the Regulation of miR-495-3p/HDAC4 Pathway - Sihui Chen; Minghong Wang; Rui Jian; Hui Li; Guoli Liu; Cuiyun Zhou; Yan Xiong; Wenqian Wang (Biochemical Genetics, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

Changes in PM2.5-related health burden in China's poverty and non-poverty areas during 2000–2020: A health inequality perspective - Yan Li; Baojie Li; Hong Liao; Bing-Bing Zhou; Jing Wei; Yuxia Wang; Yuzhu Zang; Yang Yang; Rui Liu; Xiaorui Wang (Science of The Total Environment, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Sodium hydrosulfide alleviates aluminum toxicity in Brassica napus through maintaining H2S, ROS homeostasis and enhancing aluminum exclusion - Yan Yu; Jia Dong; Rui Li; Xue Zhao; Zonghe Zhu; Fugui Zhang; Kejin Zhou; Xianyong Lin (Science of The Total Environment, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

A new process to further remove dissolved organic matter and disinfection by-product formation potential during drinking water treatment - Chongtian Lei; Yurong Chen; Aimin Li; Rui Gao; Ziang Zhang; Junxia Chen; Peng Shi; Qing Zhou; Yan Ma (Environmental Science and Pollution Research, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

U-net Models Based on Computed Tomography Perfusion Predict Tissue Outcome in Patients with Different Reperfusion Patterns - Yaode He; Zhongyu Luo; Ying Zhou; Rui Xue; Jiaping Li; Haitao Hu; Shenqiang Yan; Zhicai Chen; Jianan Wang; Min Lou (Translational Stroke Research, 2022)

Optimization of the induction, germination, and plant regeneration system for somatic embryos in apomictic walnut (Juglans regia L.) - Hongcheng Fang; Yuhui Dong; Rui Zhou; Qingpeng Wang; Qicheng Duan; Changxi Wang; Yan Bao; Shengyi Xu; Xinya Lang; Shasha Gai; Rong Chen; Ke Qiang Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Screening and Characterization of Potential Antioxidant Probiotics Isolated from the Gut of Hybrid Grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Qian Zhang; Yan Cai; Zihan Chen; Huizhong Shi; Yongcan Zhou; Yang Yang; Rui Tu; Guisen Chen; Shifeng Wang (Frontiers in Marine Science, 2022)
Some symbiotic probiotics have antioxidant activities and could improve the antioxidant capacity of the host. There is still no report on the screening of host-derived antioxidant probiotics for grouper farming. In this study, 369 out of 583 isolates were screened from the gut of hybrid grouper ( Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ ) based on their non-hemolytic characteristics. Subsequent preliminary screening with 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) scavenging rate assay resulted in 36 potential antioxidant isolates. After comprehensive evaluation with nine different antioxidant assays (DPPH scavenging rate, 2,2’-azino-bis (3-ethylbezothiazoline)-6-sulfonic acid radical scavenging rate, iron ion reducing ability, reducing activity, O 2 - · scavenging rate,·OH scavenging rate, ferrous ion chelating rate, hydrogen peroxide tolerance, oxygen-free radical scavenging ability, et al.), 10 isolates with strong antioxidant abilities were screened from 36 potential antioxidant isolates. Then some other probiotic properties, such as simulated gastrointestinal fluid tolerance, adhesion, digestive enzyme activity, and antibacterial activity of the 10 selected isolates were evaluated. All 10 isolates were also identified using the molecular method. Finally, Vibrio rhodolitus GO 91 and Shewanella corallii GO 310, as representatives of the two genera resulting from the identification of the 10 isolates, and with the best overall probiotic properties, were selected from the 10 isolates. Isolates GO 91 and GO 310 were further tested for their safety performances. Antibiotic sensitivity tests showed that GO91 and GO310 were sensitive to many commonly used aquaculture antibiotics. The in vivo challenge test of GO 91 and GO 310 didn’t cause any disease symptoms or death in hybrid grouper. Therefore, isolates GO 91 and GO 310 showed great potential to be used as probiotics in hybrid grouper farming.

Erratum to: Tracing environmental lead sources on the Ao mountain of China using lead isotopic composition and biomonitoring - Zhong-xiang Xiang; Hai-jian Bing; Yan-hong Wu; Jun Zhou; Rui Li; Xiao-li He (Journal of Mountain Science, 2022)

Geochronology, Geochemistry and Geological Significance of Volcanic Rocks of the Bangba District, Western Segment of the Central Lhasa Subterrane - Yan Cao; Zhiqiang Kang; Feng Yang; Tong Zhou; Dongmei Liu; Rui Wang (Journal of Earth Science, 2022)

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Oceaniglobus trochenteri sp. nov., isolated from the gut microflora of top shell (Trochus maculatus Linnaeus) - Zhuo Chen; Shuai-Ting Yun; Ming-Jing Zhang; Rui Yin; Yan-Xia Zhou (Archives of Microbiology, 2021)

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

Coupling anammox with heterotrophic denitrification for enhanced nitrogen removal: A review - Shenbin Cao; Rui Du; Yan Zhou (Critical Reviews in Environmental Science and Technology, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Hybrid Partition-Based Patrolling Scheme for Maritime Area Patrol with Multiple Cooperative Unmanned Surface Vehicles - Jiajia Xie; Rui Zhou; Jun Luo; Yan Peng; Yuan Liu; Shaorong Xie; Huayan Pu (Journal of Marine Science and Engineering, 2020)
Multi-robot cooperative patrolling systems have been extensively employed in the civilian and military fields, including monitoring forest fires, marine search-and-rescue, and area patrol. Multi-robot area patrol problems refer to the activity that a team of robots works cooperatively and regularly to visit the key targets in the given area for security. Following consideration of the low cost and high safety of unmanned surface vehicles (USV), a team of USVs is organized to perform area patrol in a sophisticated maritime environment. In this paper, we establish a mathematical model considering the characteristics of the cooperative patrol task and the limited conditions of USVs. A hybrid partition-based patrolling scheme is proposed for a multi-USV system to visit targets with different importance levels in a maritime area. Firstly, a centralized area partition algorithm is utilized to partition the patrolling area according to the number of USVs. Secondly, a distributed path planning algorithm is applied to planning the patrolling path for each USV to visit the targets in a maritime environment to minimize the length of the patrolling path for the USV team. Finally, comparative experiments between the proposed scheme and other methods are carried out to validate the performance of the hybrid partition-based patrolling scheme. Simulation results and experimental analysis show the efficiency of the proposed hybrid partition-based patrolling scheme compared to several previous patrolling algorithms.

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Decreased miR-325-5p Contributes to Visceral Hypersensitivity Through Post-transcriptional Upregulation of CCL2 in Rat Dorsal Root Ganglia - Rui Wu; Ping-An Zhang; Xuelian Liu; Yuan Zhou; Meijie Xu; Xinghong Jiang; Jun Yan; Guang-Yin Xu (Neuroscience Bulletin, 2019)

Effect of genotype and environment on agronomical characters of common vetch (Vicia sativa L.) - Rui Dong; Shu H. Shen; Mohamed Z. Z. Jahufer; De K. Dong; Dong Luo; Qiang Zhou; Xu T. Chai; Kai Luo; Zhi B. Nan; Yan R. Wang; Zhi P. Liu (Genetic Resources and Crop Evolution, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Effects of frequency and confining pressure on consolidation drainage behavior of soft marine clays - Yong-Hong Miao; Fan-Bo Zhou; Jie Yin; Yan-Chang Sun; Rui-Bing Li; Jian-Fei Lu (Marine Georesources & Geotechnology, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

The IMPDH inhibitors, ribavirin and mycophenolic acid, inhibit peste des petits ruminants virus infection - Qiu-yan Chang; Fu-cheng Guo; Xue-rui Li; Jian-hua Zhou; Xuepeng Cai; Qiuwei Pan; Xiao-xia Ma (Veterinary Research Communications, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Genomic changes in an attenuated genotype I Japanese encephalitis virus and comparison with virulent parental strain - Yuyong Zhou; Rui Wu; Yao Feng; Qin Zhao; Xintian Wen; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; Sanjie Cao (Virus Genes, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Mutation of I176R in the E coding region weakens Japanese encephalitis virus neurovirulence, but not its growth rate in BHK-21 cells - Yuyong Zhou; Rui Wu; Qin Zhao; Yung-Fu Chang; Xintian Wen; Yao Feng; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Archives of Virology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Attenuation of ethanol abstinence-induced anxiety- and depressive-like behavior by the phosphodiesterase-4 inhibitor rolipram in rodents - Mei-Fang Gong; Rui-Ting Wen; Ying Xu; Jian-Chun Pan; Ning Fei; Yan-Meng Zhou; Jiang-Ping Xu; Jian-Hui Liang; Han-Ting Zhang (Psychopharmacology, 2017)

Tracing environmental lead sources on the Ao mountain of China using lead isotopic composition and biomonitoring - Zhong-xiang Xiang; Hai-jian Bing; Yan-hong Wu; Jun Zhou; Rui Li; Xiao-li He (Journal of Mountain Science, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Suppressing Receptor-Interacting Protein 140: a New Sight for Salidroside to Treat Cerebral Ischemia - Tong Chen; Zhanqiang Ma; Lingpeng Zhu; Wenjiao Jiang; Tingting Wei; Rui Zhou; Fen Luo; Kai Zhang; Qiang Fu; Chunhua Ma; Tianhua Yan (Molecular Neurobiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Cloning and molecular characterization of Myb transcription factors from Leymus (Poaceae: Trticeae) - Ying-xia Lei; Yan Zhang; Yang-yi Li; Jian-Jun Lai; Gang Gao; Hai-qin Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Salidroside suppresses inflammation in a D-galactose-induced rat model of Alzheimer’s disease via SIRT1/NF-κB pathway - Jin Gao; Rui Zhou; Xintong You; Fen Luo; He He; Xiayun Chang; Lingpeng Zhu; Xuansheng Ding; Tianhua Yan (Metabolic Brain Disease, 2016)

Effects of climate change on potential habitats of the cold temperate coniferous forest in Yunnan province, southwestern China - Wang-jun Li; Ming-chun Peng; Motoki Higa; Nobuyuki Tanaka; Tetsuya Matsui; Cindy Q. Tang; Xiao-kun Ou; Rui-wu Zhou; Chong-yun Wang; Hai-zhong Yan (Journal of Mountain Science, 2016)

Two new triterpenoid glycosides from the stems of Camellia oleifera Abel - Qing-Wei Yan; Hui-Zheng Fu; Yue-Hua Luo; Guo-Ping Zhou; Kai-Hua Wan; Rui-Jian Zhong (Natural Product Research, 2016)

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

The cardioprotective effect of salidroside against myocardial ischemia reperfusion injury in rats by inhibiting apoptosis and inflammation - Lingpeng Zhu; Tingting Wei; Jin Gao; Xiayun Chang; He He; Fen Luo; Rui Zhou; Chunhua Ma; Yu Liu; Tianhua Yan (Apoptosis, 2015)

Meiothermus roseus sp. nov., a thermophilic bacterium isolated from a geothermal area - Hong Ming; Yan-Yan Duan; Qian-Qian Guo; Yi-Rui Yin; En-Min Zhou; Lan Liu; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Effects of Lettuce Glycoside B in Ameliorating Pulmonary Fibrosis Induced by Irradiation Exposure and its Anti-Oxidative Stress Mechanism - Yan Zhou; Yuan Gao; Yingying Chen; Rui Zheng; Wei Zhang; Mingqi Tan (Cell Biochemistry and Biophysics, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

piggyBac transposon-derived targeting shRNA interference against the Bombyx mori nucleopolyhedrovirus (BmNPV) - Fang Zhou; Rui-ting Chen; Yan Lu; Shuang Liang; Mei-xian Wang; Yun-gen Miao (Molecular Biology Reports, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

The effect of NF-κB antisense oligonucleotide on transdifferentiation of fibroblast in lung tissue of mice injured by bleomycin - Yan Zhou; Xiaoye Zhang; Mingqi Tan; Rui Zheng; Li Zhao (Molecular Biology Reports, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Soluble N-terminal fragment of mutant Huntingtin protein impairs mitochondrial axonal transport in cultured hippocampal neurons - Jun Tian; Ya-Ping Yan; Rui Zhou; Hui-Fang Lou; Ye Rong; Bao-Rong Zhang (Neuroscience Bulletin, 2014)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Highly Efficient Removal of Cu(II) from Aqueous Solution by Using Graphene Oxide - Wenqin Wu; Yan Yang; Haihui Zhou; Tingting Ye; Zhongyuan Huang; Rui Liu; Yafei Kuang (Water, Air, & Soil Pollution, 2013)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

The promotion of clean development mechanism to cement industry capturing waste heat for power generation in China - Qishe Yan; Chang-Bo Zhou; Peng Qu; Rui-qin Zhang (Mitigation and Adaptation Strategies for Global Change, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Detection of known mutations in hypertrophic cardiomyopathy using oligonucleotide microarrays assisted by improved base stacking hybridization - Dong Wang; Yan Li; Rui Zhang; Di Jiang; Xuemei Ma; Yuxiang Zhou; Jing Cheng (Biotechnology Letters, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)